Pulse-response measurement of frequency-resolved water dynamics on a hydrophilic surface using a Q-damped atomic force microscopy cantilever - Kageshima, Masami (Beilstein-Institut, 2012)
The frequency-resolved viscoelasticity of a hydration layer on a mica surface was studied by pulse-response measurement of a magnetically driven atomic force microscopy cantilever. Resonant ringing of the cantilever due to its 1st and 2nd resonance modes was suppressed by means of the Q-control technique. The Fourier–Laplace transform of the deflection signal of the cantilever gave the frequency-resolved complex compliance of the cantilever–sample system. The significant viscoelasticity spectrum of the hydration layer was successfully derived in a frequency range below 100 kHz by comparison of data obtained at a distance of 300 nm from the substrate with those taken in the proximity of the substrate. A positive value of the real part of the stiffness was determined and is attributed to the reported solidification of the hydration layers.